State of the Art Artificial Neural Network, Deep Learning, and the Future Generation - Ahmed, Munef Abdullah; Trausan-Matu, Stefan (Indian Journal of Computer Science, 2017)
The use of the neural networks or artificial intelligence or deep learning in its broadest and most controversial sense has been a tumultuous journey involving three distinct hype cycles and a history dating back to the 1960s. Resurgent and enthusiastic interest in machine learning and its applications bolster the case for machine learning as a fundamental computational kernel. Furthermore, researchers have demonstrated that machine learning can be utilized as an auxiliary component of applications to enhance or enable new types of computation such as approximate computing or automatic parallelization. In our view, machine learning becomes not the underlying application, but a ubiquitous component of applications. In recent years, deep learning in artificial neural networks (ANN) has won numerous contests in pattern recognition and machine learning; this view necessitates a different approach towards the deployment of ANN and deep learning.